Arthur and the forbidden city - Besson, Luc 1959- (HarperCollinsPublishers, 2005)
In order to find his grandfather's lost treasure and save the Minimoys, Arthur and his companions, including Princess Selinia, travel into the forbidden city ruled by Maltazard the Cursed
"Originally published in France under the title Arthur et la cité interdite by Intervista/Manitoba in 2003.". - Sequel to: Arthur and the Minimoys
Keywords: Grandparent and child / Juvenile fiction; Magic / Juvenile fiction; Treasure troves / Juvenile fiction; Adventure stories; Size / Juvenile fiction; Kings, queens, rulers, etc / Juvenile fiction; Fantasy fiction / Juvenile fiction; Grandparent and child / Fiction; Magic / Fiction; Buried treasure / Fiction; Adventure and adventurers / Fiction; Size / Fiction; Kings, queens, rulers, etc / Fiction; Fantasy